Prevalence and health seeking behaviour of urinary incontinence among postmenopausal women attending outpatient clinic Hospital Universiti Sains Malaysia - Mokti, Shakiroh Abdul (2017)
Introduction: Urinary incontinence (UI) is common in adult women, but under diagnosed and under treated. Menopause leads to urogenital atrophy due to decline in estrogen which causes UI. Postmenopausal women often delay in seeking treatment. There were also limited studies conducted of UI among postmenopausal women. Objectives: The objective of this study is to determine the prevalence of urinary incontinence and the health-seeking behaviour of postmenopausal women and their associated factors. Methodology: A cross sectional study was carried out involving 348 postmenopausal women between 47 till 82 years old attended outpatient clinic from February 2015 to April 2015 through convenience sampling method. Every participant was given a validated self-administered Questionnaire Survey formulated by a panel of experts from the Asia-Pacific Continence Advisory Board (APCAB), which had Cronbach’s alpha of 0.64. It consisted of three parts assessing sociodemographic data, urinary incontinence and health-seeking behaviour. Results: The mean age of respondents was 67.4 (±5.8) years old. The majority of them had menopause for more than 5 years (70.4%) and attained at leastsecondary education (61.7%). The prevalence of urinary incontinence was 58.9% with 24.9% having moderate and 7.8% severe UI. The most common type of UI was stress incontinence (83.4%). Only higher family income was significantly associated with UI (adjusted odds ratio [OR] 0.32, 95% confidence interval [CI]: 0.12, 0.85). Only 13.17% of patients with UI sought treatment. Factors significantly associated with health seeking behaviour were age of menopause (adjusted odds ratio [OR] 0.88, 95% confidence interval [CI]: 0.79, 0.97) and severe UI (adjusted odds ratio [OR] 9.50, 95% confidence interval [CI]: 1.84, 49.08). Conclusion: The prevalence of UI among postmenopausal women attending Outpatient clinic was unexpectedly high, yet only a few sought treatment. This should promote both health care providers and women to a larger alertness of the situation.